Pengaruh Pemahaman SAK EMKM, Literasi Keuangan Pelaku Usaha Dan Pemanfaatan Teknologi Informasi Terhadap Kualitas Laporan Keuangan UMKM Di Kota Medan - Hariyatih, Suri; Rahmani, Nur Ahmadi Bi; Nurbaiti, Nurbaiti (Fakultas Ekonomi Prodi Akuntansi, 2026)
This study aims to analyze the influence of SAK EMKM understanding, business actors' financial literacy, and the utilization of information technology on the quality of MSME financial reports in Medan City. The research method used is quantitative, with data collection techniques through questionnaires distributed to 100 MSME respondents selected using a purposive sampling method with specific criteria. Data were analyzed using multiple linear regression with the assistance of SPSS software. The partial research results indicate that the understanding of SAK EMKM does not have a significant effect on the quality of financial reports. Conversely, financial literacy and the utilization of information technology have a positive and significant influence on the quality of financial reports. Simultaneously, these three variables have a significant effect with a coefficient of determination (Adjusted R Square) of 79.2%, while the remaining 20.8% is influenced by other factors outside this research model. These results imply that strengthening financial literacy and the adoption of information technology are key factors in increasing the transparency and accountability of MSME financial reporting in Medan City. Keywords: Financial Literacy, Financial Reports, Information Technology, MSMEs, SAK EMKM